Effect of gusty wind on road tunnel safety - Suban, Aleš (Strojniški vestnik, 2015)
This article deals with the effect of wind with its characteristics on the longitudinal ventilation of a road tunnel as a key segment of fire safety. Using CFD simulations, the influence of wind gusts, which differ and is more difficult to define than the influence of a constant wind on tunnel ventilation, is researched in more detail. On the basis of the simulation results, which have been validated with real measures, the findings are presented regarding the importance of taking into account the characteristics of non-stationary wind to ensure the adequate safety of tunnel users in the event of a fire, as well as of fire-fighting units during intervention.
Keywords: burja; cestni predori; CFD simulacije; Kastelec (predor); program FDS; vetrovi s sunki; vzdolžno prezračevanje